FORMATION OF PERSONAL AND PROFESSIONAL QUALITIES IN THE PREPARATION OF THE FUTURE TEACHER - G.A PICHUGINA; E.B.K ABDULAEVA (Хуманитарни Балкански изследвания, 2021)
Existing trends in modern society require specialists in professional activities to have a high level of proficiency not only in strictly professional skills, but also specialists who are ready to work in non-traditional conditions. Therefore, in the field of education, teachers of an innovative type are increasingly required. Their activities are associated not only with the organization of the educational process, but also with self-improvement, self-development, mobility, creativity, and the expression of individuality. A contradiction arises between the need of society for specialists in the field of education, who possess not only the amount of theoretical knowledge, but also the personal and professional qualities of a teacher and traditional approaches to his training at a university. In this regard, the task of higher educational institutions for the preparation of future teachers is the theoretical training and development of the student's personal and professional qualities. The article proposes to change the approaches to conducting lectures. We recommend using modern pedagogical technologies in the course of the lecture, which will allow students not only to master the theoretical material, but also to acquire skills in working with the audience. In the course of classroom training for a student of a pedagogical orientation, systematically create conditions for the development of his personal and professional qualities and conditions for the development of motivation in acquiring pedagogical abilities.